Pengaruh Fear of Missing Out Terhadap Perilaku Phubbing Pada Remaja Pengguna Smartphone di Kota Bekasi. - Marpaung, Dedi Ramadan; Rahmi, Kus Hanna (Jurnal Ilmiah Wahana Pendidikan, 2024)
Teenagers who use smartphones when communicating with other people cause the person they are talking to to feel ignored, which is called Phubbing Behavior. When teenagers feel fear of missing out, teenagers check their smartphones regularly, especially at Bekasi City. The variables in this study were measured using two measuring instrument, namely the Fear of Missing Out measuring instrument and the Phubbing Behavior measuring instrument, which focuses on a Likert Scale model that has been modified using five alternative answer choices. The result of the regression test obtained the equation Y = (21.588 + 0.344). This mean the equality of the phubbing behavior variable and the fear of missing out variable. Based on the result of the ANOVA test, a significant value of 0.000 was obtained, which means that there is an influence of Fear of Missing Out on Phubbing Behavior in adolescene smartphone’s user. The result of R square (R2) show a figure of 0.174 which means that the variables Fear of Missing Out make an effective contribution of 17.4% to Phubbing Behavior. Meanwhile, the remaining 82.6% is influenced by other factors.